A dendritic β-galactosidase-responsive folate–monomethylauristatin E conjugate. Issue 87 (14th September 2015) - Alsarraf, Jérôme; Péraudeau, Elodie; Poinot, Pauline; Tranoy-Opalinski, Isabelle; Clarhaut, Jonathan; Renoux, Brigitte; Papot, Sébastien
Abstract : We designed a dendritic folate–drug conjugate allowing the β-galactosidase-catalysed release of two MMAE molecules inside folate receptor-positive cancer cells. Abstract : We report the study of a new drug delivery system programmed for the selective internalisation and the subsequent enzyme-catalysed release of two monomethylauristatin E molecules inside FR-positive cancer cells. This targeting device is the most potent β-galactosidase-responsive folate–drug conjugate developed so far, killing cancer cells expressing a medium level of FR at low nanomolar concentrations.